1998
DOI: 10.1177/146135579800100306
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Conflict Resolution Tactics of Male and Female Police Patrol Officers

Abstract: This study examined the conflict resolution tactics of male and female police officers on patrol. An instrument for measuring behavioural tactics was developed from a theoretical model of conflict resolution. Male and female officers were observed when interacting with members of the public, and their behaviour was recorded in real time via a datalogger. Lag sequential analysis was used to detect sequences of behaviour. Results indicated that male officers used coercive tactics, such as controlling statements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Bloch & Anderson 1974;CJC 1998), as has research into the impact of women on styles of police work and conduct (e.g. Braithwaite & Brewer 1998;Grennan 1987;Kennedy & Homant 1983;Waugh et al 1998). The issue of citizen attitudes toward women police has also been largely resolved in favour of equality (Koenig & Juni 1981;Winnard 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Bloch & Anderson 1974;CJC 1998), as has research into the impact of women on styles of police work and conduct (e.g. Braithwaite & Brewer 1998;Grennan 1987;Kennedy & Homant 1983;Waugh et al 1998). The issue of citizen attitudes toward women police has also been largely resolved in favour of equality (Koenig & Juni 1981;Winnard 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It also assists with the analysis of situational factors that are involved in the encounter and its outcomes. Similar approaches have since been used to analyze police use-of-force transactions and to measure the effect that one utterance has on the outcome of an encounter (Braithwaite and Brewer, 1998;Terrill, 2005;Terrill and Mastrofski, 2002). Utterances by a police officer and strings of utterances have also been analyzed to measure how the action of one actor affects another (Sykes and Brent, 1983;Terrill, 2005;Toch, 1969).…”
Section: Previous Research On Assaults On Police Officersmentioning
confidence: 99%
“…Interestingly, while masculinity is often described as a cultural dimension, research exploring officer demeanor and the use of force often finds that gender itself (an individual factor) is a significant factor. Braithwaite and Brewer (1998) showed female officers to be less coercive and confrontational in their demeanor toward citizens. Research has shown that female officers use less force against citizens (Bazley, Lersch, & Mieczkowski, 2007; Rabe-Hemp, 2008) and receive fewer complaints about their behavior (Lonsway et al., 2002; Waugh, Ede, & Alley, 1998), while younger male officers are more likely to use excessive force (Lersch & Mieczkowski, 2005; Porter & Prenzler, 2015).…”
Section: Masculinity Crime Fighting and Aggressionmentioning
confidence: 99%